Chemical constituents of the essential oils of Xylopia caudata hook F.E.T. thoms. - Nor Azah Mohamad Ali,; Ibrahim Jantan,; Sri Nurestri Abd. Malek ,; Zuriati Zakaria, (Universiti Kebangsaan Malaysia, 1996)
The chemical compositions of the leaf and bark oils of Xylopia caudata were examined by co-chromatography with authentic samples on a polar capillary column (PEG 20M) and a non polar capillary column (SE-30), GC/MS and further comparison with Kovats Retention Index. The essential oils were mainly made up of monoterpenoids. The major components in both oils were β-pinene, α-pinene, limonene and a-terpineol which collectively represented 90% and 69% of the leaf and bark oils respectively.